RISK FACTORS ASSOCIATED WITH PREECLAMPSIA IN PREGNANT WOMEN (PARITY, OBESITY, MULTIPLE PREGNANCY, HISTORY OF HYPERTENSION AND AGE WITH THE PREVALENCE OF PREECLAMPSIA AT SYAMRABU BANGKALAN HOSPITAL, BANGKALAN IN 2022 - Hamimatus zainiyah; Dwi Wahyuning Tyas; Heni Ekawati; Zuryaty Zuryaty (NHM PRESS, 2023)
Background: Preeclampsia is a complication of pregnancy that is characterized by hypertension, edema, and proteinuria. This syndrome usually appears in the second to the third trimester of pregnancy. In East Java, preeclampsia is the dominant factor causing maternal mortality. Based on a preliminary study at Syamrabu Bangkalan Hospital, the incidence of preeclampsia was 35% of all referral cases. Objective: This research aimed to analyze the high-risk factors for preeclampsia in pregnant women (parity, obesity, multiple pregnancies, history of hypertension, and age with the incidence of preeclampsia at Syamrabu Bangkalan Hospital in 2022 Methods: This research was quantitative with a cross-sectional approach. The population in this study were all pregnant women recorded in the medical records of Syamrabu Bangkalan Hospital in 2022, as many as 204 pregnant women. The sample in this study was 162 respondents. Samples were taken from the data using a systematic random sampling system and analyzed using the Chi-Square statistical test. The analysis used univariate and bivariate analysis. The time of the study was conducted on July 01-09, 2022. Results: Based on the chi-square test, there is a significant relationship between high-risk factors for preeclampsia (parity, obesity, multiple pregnancies, history of hypertension, and age with the incidence of preeclampsia in pregnant women at Syamrabu Hospital Bangkalan in 2022. Conclusion: The results of this study are expected to prevent the incidence of preeclampsia in pregnant women early in an effort to reduce the incidence of preeclampsia, morbidity, and mortality in mothers and babies due to existing pregnancy complications such as preeclampsia